New Directions in Immigration Policy: Canada's Evolving Approach to the Selection of Economic Immigrants - Ana Ferrer; Garnett Picot; W. Craig Riddell (Institute for the Study of Labor (IZA), 2014)
Canada's immigration system is currently undergoing significant change driven by several goals that include (1) a desire to improve the economic outcomes of entering immigrants; (2) an attempt to better respond to short-term regional labor market shortages often associated with commodity booms, and (3) a desire to shift immigration away from the three largest cities to other regions of the country. These goals reflect the implementation of new immigration programs in the 2000s. The paper discusses the recent changes to Canadian immigration policy, examines preliminary evaluations of the new programs and discusses potential future issues emanating from the changes.
Keywords: J11; J24; J61; J68; 330; migration; immigration policy; immigrant selection; points system; human capital; temporary foreign workers